The Influence of the Composite Indicator of the Human Development Index on Economic Growth in West Nusa Tenggara Province 2013 – 2023 - Amanda Anjani Agustina; St. Maryam; Helmy Fuadi (Indonesian Development Economics and Localities, 2025)
This study investigates the relationship between economic growth and human development indicators in West Nusa Tenggara Province during the period of 2013–2023. Using a quantitative descriptive approach, the research utilizes secondary time series data collected through library research and documentation techniques from official institutions. The variables include Economic Growth (dependent) and four independent variables representing the dimensions of the Human Development Index (HDI): Life Expectancy, Average Years of Schooling, Expected Years of Schooling, and Per Capita Expenditure. Multiple linear regression analysis, supported by classical assumption tests and statistical evaluations (t-test, F-test, and adjusted R2), is employed to examine the data. The results indicate that, both partially and simultaneously, the HDI components do not have a significant effect on economic growth, suggesting an indirect relationship. The findings highlight the need for policy interventions that enhance the economic sector's value-added potential to promote job creation and improve HDI in the region.